Burn trauma in infants - Yasemin Demir Yiğit; Ebral Yiğit; Ilhan Taş (SpringerOpen, 2023)
Abstract Background A wealth of data exists concerning pediatric burn epidemiology in general, but more is explicitly needed in infants under 1 year of age, a particular group in which mobility begins to develop. Methods In this study,206 patients followed up for burns in Diyarbakır Gazi Yaşargil Training and Research Hospital Burn Center between January 2016 and September 2021 were included in the study. Results Of the patients, 120 (58.3%) were male, and 86 (41.7%) were female. The mean age was 10.0 ± 2.0 months. The total number of cases ranged from 3 to 12 months, with the incidence of burns peaking at 12 months. When we look at the etiology of burns, scalding burns were the most common, with 184 (89.3%) cases. Most of the burns occurred in the kitchen because their mothers and children spent a lot of time there. It was positive in 23.8% of the wound culture results obtained with a punch biopsy. Staphylococcus aureus was the most abundant microorganism in wound culture results, with 5.8%. The mean hospital stay of the patients was 4.99 ± 3.67 days. Our mortality rate was 1.94% (n:4). Conclusion In conclusion, As preventive measures, it is necessary to increase protective measures at home and to raise awareness of families about burn etiologies.